Comparative Analysis of PSO Algorithms for PID Controller Tuning - Štimac, Goranka; Braut, Sanjin; Žigulić, Roberto (Chinese journal of mechanical engineering, 2014)
The active magnetic bearing（AMB）suspends the rotating shaft and maintains it in levitated position by applying controlled electromagnetic forces on the rotor in radial and axial directions.Although the development of various control methods is rapid,PID control strategy is still the most widely used control strategy in many applications,including AMBs.In order to tune PID controller,a particle swarm optimization（PSO）method is applied.Therefore,a comparative analysis of particle swarm optimization（PSO）algorithms is carried out,where two PSO algorithms,namely（1）PSO with linearly decreasing inertia weight（LDW-PSO）,and（2）PSO algorithm with constriction factor approach（CFA-PSO）,are independently tested for different PID structures.The computer simulations are carried out with the aim of minimizing the objective function defined as the integral of time multiplied by the absolute value of error（ITAE）.In order to validate the performance of the analyzed PSO algorithms,one-axis and two-axis radial rotor/active magnetic bearing systems are examined.The results show that PSO algorithms are effective and easily implemented methods,providing stable convergence and good computational efficiency of different PID structures for the rotor/AMB systems.Moreover,the PSO algorithms prove to be easily used for controller tuning in case of both SISO and MIMO system,which consider the system delay and the interference among the horizontal and vertical rotor axes.